An Anatomical Site and Genetic-Based Prognostic Model for Patients With Nuclear Protein in Testis (NUT) Midline Carcinoma: Analysis of 124 Patients. Issue 2 (6th November 2019) - Chau, Nicole G; Ma, Clement; Danga, Kristina; Al-Sayegh, Hasan; Nardi, Valentina; Barrette, Ryan; Lathan, Christopher S; DuBois, Steven G; Haddad, Robert I; Shapiro, Geoffrey I; Sallan, Stephen E; Dhar, Arindam; et al.
Abstract: Background: NUT midline carcinoma, renamed NUT carcinoma (NC), is an aggressive squamous cancer defined by rearrangement of the NUTM1 gene. Although a subset of patients can be cured, for the majority of patients the prognosis is grim. We sought to classify patients into risk groups based on molecular and clinicopathologic factors at the time of diagnosis. Methods: Clinicopathologic variables and survival outcomes were extracted for a total of 141 NC patients from the NUT midline carcinoma Registry using questionnaires and medical records. Translocation type was identified by molecular analyses. Survival tree regression analysis was performed to determine risk factors associated with overall survival (OS). Results: For 141 patients, the median age at diagnosis was 23.6 years. Fifty-one percent had thoracic origin compared with 49% nonthoracic sites (41% head and neck, 6% bone or soft tissue, 1% other). The median OS was 6.5 months (95% confidence interval [CI] = 5.8 to 9.1 months). Most patients had the BRD4-NUTM1 fusion (78%), followed by BRD3-NUTM1 (15%) and NSD3-NUTM1 (6%). Survival tree regression identified three statistically distinct risk groups among 124 patients classified by anatomical site and genetics: group A is nonthoracic primary, BRD3-, or NSD3-NUT (n = 12, median OS = 36.5 months, 95% CI = 12.5 to not reported months); group B is nonthoracic primary, BRD4-NUT (n = 45, median OS = 10 months, 95% CI = 7 to 14.6 months); and group C is thoracic primary (n = 67, median OS = 4.4 months, 95% CI = 3.5 to 5.6 months). Only groups A and B had long-term (≥3 years, n = 12) survivors. Conclusions: We identify three risk groups defined by anatomic site and NUT fusion type. Nonthoracic primary with non- BRD4-NUT fusion confers the best prognosis, followed by nonthoracic primary with BRD4-NUT . Thoracic NC patients, regardless of the NUT fusion, have the worst survival.